The prevalence and clinical characteristics of pertussis-associated pneumonia among infants in Botswana - Bahaa Abu-Raya; David M. Goldfarb; Marek Smieja; Kathy Luinstra; Melissa Richard-Greenblatt; Andrew P. Steenhoff; Kristen A. Feemster; Tonya Arscott-Mills; Coleen K. Cunningham; Samir S. Shah; Mohamed Zaakir Patel; Matthew S. Kelly; et al. (BMC Pediatrics, 2019)
Abstract Background There are scant data on the prevalence and clinical course of pertussis disease among infants with pneumonia in low- and middle-income countries. While pertussis vaccination coverage is high (≥90%) among infants in Botswana, human immunodeficiency virus (HIV) infection affects nearly one-third of pregnancies. We aimed to evaluate the prevalence and clinical course of pertussis disease in a cohort of HIV-unexposed uninfected (HUU), HIV-exposed uninfected (HEU), and HIV-infected infants with pneumonia in Botswana. Methods We recruited children 1–23 months of age with clinical pneumonia at a tertiary care hospital in Gaborone, Botswana between April 2012 and June 2016. We obtained nasopharyngeal swab specimens at enrollment and tested these samples using a previously validated in-house real-time PCR assay that detects a unique sequence of the porin gene of Bordetella pertussis. Results B. pertussis was identified in 1/248 (0.4%) HUU, 3/110 (2.7%) HEU, and 0/33 (0.0%) HIV-infected children. All pertussis-associated pneumonia cases occurred in infants 1–5 months of age (prevalence, 1.0% [1/103] in HUU and 4.8% [3/62] in HEU infants). No HEU infants with pertussis-associated pneumonia were taking cotrimoxazole prophylaxis at the time of hospital presentation. One HUU infant with pertussis-associated pneumonia required intensive care unit admission for mechanical ventilation, but there were no deaths. Conclusions The prevalence of pertussis was low among infants and young children with pneumonia in Botswana. Although vaccination against pertussis in pregnancy is designed to prevent classical pertussis disease, reduction of pertussis-associated pneumonia might be an important additional benefit.